Integrating geographic information into survey research: current applications, challenges and future avenues - Blümke, Matthias; Resch, Bernd; Lechner, Clemens; Westerholt, René; Kolb, Jan-Philipp (Survey research methods, 2017)
Geographic information science (GIScience) offers survey researchers a plethora of rapidly evolving research strategies and tools for data acquisition and analysis. However, the potential for incorporating geographic information systems (GIS) tools into traditional survey research has not yet been fully appreciated by survey researchers. In this article, we provide a comprehensive overview of recent advances and challenges in leveraging this potential. First, we present state-of-the-art applications of GIS tools in traditional survey research, drawing mainly on examples from psychological survey research (e.g., socioecological psychology). We also discuss innovative GIS tools (e.g., wearables) and GIScience methods (e.g., citizen sensing) that expand the scope of traditional surveys. Second, we highlight a number of challenges and problems (e.g., choice of spatial scale, statistical issues, privacy concerns) and - where possible - suggest remedies. With increasing awareness of the potential that GIS tools hold for survey research, and intensified dialogue between researchers from both sides, more fruitful collaboration appears within reach